Nikos Nikolaidis de Chypre - Caravolas, Jean Antoine (Études helléniques / Hellenic Studies, 2011)
Although Nikos Nikolaidis, the Cypriot (1884-1956), was in his time acclaimed as a master short-story writer and a distinguished painter, he often in his older age complained to be neglected, if not forgotten, by critics his peers and the general public. My research proves the contrary. Nikolaidis was admitted to the Pantheon of Modern Greek literature already during his lifetime and his literary work continues to be published, discussed, translated and honoured in many countries. As I hope to have shown in this paper, if Nikolaidis is still remembered it is not only because he was an excellent writer but equally because of his personality, the kindness, integrity and noblesse of his character, all qualities that permeated his writings, his paintings and his attitude towards all human beings.